Anxiety sensitivity and dimensions of perfectionism in children and adults - Lauri Korajlija, Anita (Array, 2009)
Perfectionist thinking includes a belief that fear of possible anxiety symptoms is evidence of imperfection. The aim of this study was to examine the relationship between dimensions of anxiety sensitivity (AS) and dimensions of positive and negative perfectionism. Using the sample of 1585 children and 1541 adults, we measured anxiety sensitivity and positive and negative dimensions of perfectionism. Results demonstrate higher levels of maladaptive perfectionism in children with high AS. In adults, perfectionism is significantly higher in the group with high AS. This difference is larger in the case of negative perfectionism. Both samples showed a high positive connection between the dimensions of negative perfectionism and the dimensions of anxiety sensitivity. The connection between dimensions of positive perfectionism and anxiety sensitivity are low or insignificant. Our results confirm that AS and perfectionism correlate already in childhood, a correlation that is confirmed in adulthood. This combination could present a risk for the appearance of anxiety symptoms and other related difficulties. The practical application of these findings indicates a need for attention to both AS and perfectionism, as well as their interaction, in treatment.